Doping Tuned the Carrier Dynamics in Li-Doped Bi2Se3 Crystals Revealed by Femtosecond Transient Optical Spectroscopy - Qiya Liu; Min Zhang; Xinsheng Yang; Tixian Zeng; Minghu Pan (Nanomaterials)
Topological insulators (TIs) can be widely applied in the fields of ultrafast optical and spintronic devices owing to the existence of topologically protected gapless Dirac surface states. However, the study of ultrafast dynamics of carriers in TIs remains elusive. In this work, the carrier dynamics of Li-doped Bi2−xSe3 single crystals were investigated by femtosecond (fs) transient optical spectroscopy (ΔR/R(t) signals). The temperature dependence for the relaxation rates of the electron–electron interaction and electron–phonon coupling is consistent with the results of electrical transport, which indicates the carrier dynamics of TI is highly related with carrier concentrations. We find that the carrier type and concentration of Bi2Se3 can be tuned by Li doping, leading to a metal-insulation transition at low temperatures (T ≤ 55 K), indicating that electron–electron interactions are dominant at low temperature. For T > 55 K, electron–phonon coupling in the bulk carriers becomes the main electric transport mechanism.